KONSEP WAHYU MENURUT NASHR HAMID ABU ZAYD - Munjin, Shidqy (MAGHZA, 2019)
Abu Zayd is known as a thinker who developed a hermeneutic theory which caused him to think that the Qur'an is a human text. According to him, because the Qur'an uses cultural language and is formed in a particular cultural context, the Qur'an is a cultural product. The results of this study indicate that the concept of revelation initiated by Abu Zayd focused on the problem of the relationship between text and reality. To explain this conception, Abu Zayd described it in several approaches, such as language, culture, and history. Abu Zayd used hermeneutics as a tool to dissect ?ul?m al-Qur??n and show the various mistakes made by scholars. Studies carried out by the ulama so far have been too theocentric and have forgotten the level of reality that is the target of the Qur'an. Studies that are theocentric like this will cause bias because the resulting studies will tend to be ideological. While the study itself is considered as a study that is realistic and free from ideological tendencies because the research method rests on the empirical reality that will produce scientific and objective studies.